Barchester Towers. - Trollope, Anthony (Oxford world's classics., 1996)
Barchester Towers, Trollope's most popular novel, is the second of the six Chronicles of Barsetshire. The Chronicles follow the intrigues of ambition and love in the cathedral town of Barchester. Trollope was of course interested in the Church, that pillar of Victorian society - in its susceptibility to corruption, hypocrisy, and blinkered conservatism - but the Barsetshire novels are no more ecclesiastical' than his Palliser novels are political'. It is the behaviour of the individuals within a power structure that interests him. In this novel Trollope continues the story of Mr Harding andh.